2006
DOI: 10.2310/6670.2006.00060
|View full text |Cite
|
Sign up to set email alerts
|

Chronically Impaired Endothelial Vasoreactivity Following Oversized Endovascular Introducer Sheath Placement in Porcine Iliac Arteries: Implications for Endovascular Therapy

Abstract: The conventional endovascular aortic aneurysm procedure entails the placement of oversized introducer sheaths in relatively normal ileofemoral arteries to allow the delivery and deployment of endovascular prosthesis. Endoluminal manipulation with passage of oversized endoluminal devices can lead to endothelial denudation, resulting in impaired cellular function. The purpose of this study was to assess the time course of endothelial function with vasoreactivity following oversized endovascular sheath insertion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Of the 46 selected studies, 30, 15, and 1 reported swine, ovine, and bovine data, respectively. 2 , 10 53 In the 1 paper we found describing bovine arterial dimensions, only thoracic aorta measurements were determined to be relevant in this study. We found no study describing aortic arch branch diameters in calves and only 1 study in sheep reporting brachiocephalic trunk diameters.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 46 selected studies, 30, 15, and 1 reported swine, ovine, and bovine data, respectively. 2 , 10 53 In the 1 paper we found describing bovine arterial dimensions, only thoracic aorta measurements were determined to be relevant in this study. We found no study describing aortic arch branch diameters in calves and only 1 study in sheep reporting brachiocephalic trunk diameters.…”
Section: Resultsmentioning
confidence: 99%
“…Swine have become frequently used in preclinical studies of medical devices because of the anatomical and physiological similarities between swine and humans [3, 11, 12, 17]. Currently, ear tags and ear notches are common swine identification methods.…”
Section: Introductionmentioning
confidence: 99%